(untitled) (Historia, 2021)
The VOC-era and the development of identity consciousnesses at the Cape To what extent can it be claimed that modern South African identities took shape during the period of VOC at the Cape? This question is addressed against the background that in historiography it has often been claimed that Afrikaner identity originated in the period of Dutch rule at the Cape. In his doctoral thesis Ad Biewenga concluded that by 1730 the Cape was a Dutch colony in name and culture. This article deals with the origins of five identities of which the first footprints can be distinguished by 1795 : The Afrikaner, the Khoi and San, the mixed Cape population, the slaves and the Muslims. In the conclusion the issue of whether these identities represent a true reflection of the historical situation or a construction by modern historians is discussed. In hoe ’n mate kan daar teen 1795 van die bestaan van verskillende identiteite aan die Kaap gepraat word? Hierdie vraag word ondersoek in die lig van die feit dat die oorsprong van Afrikaneridentiteit dikwels na die Kompanjiestyd teruggevoer word. In sy doktorale studie het Ad Biewenga bevind dat die Kaap teen 1730 ’n duidelike Nederlandse identiteit vertoon het. In hierdie artikel word gelet op die oorsprong van vyf identiteite tydens die Kompanjiesbewind : ’n Afrikaanse identiteit, ’n Khoi- en Sanidentiteit, die identiteit van ’n gemengde bevolking, die slawe en ’n Moslemidentiteit.